Electrification and Household Welfare : Evidence from Pakistan - Samad, Hussain; Zhang, Fan (World Bank, Washington, DC, 2018)
As many as 50 million people in Pakistan may still live without connection to the electric grid. Pakistan also has some of the world's worst power outages. Using data from a nationally representative two-period panel survey, this paper presents the first empirical evidence on the cost of unreliable electricity supply to households in Pakistan. The results show that lack of connectivity and poor reliability may be costing the country at least $4.5 billion (1.7 percent of gross domestic product) a year. Addressing the problem requires energy sector reforms to correct regulatory and institutional distortions in the gas and electricity sectors.